Parisitisme des Loranthaceae sur lavocatier (Persea americana, Lauraceae) dans la region de Yaounde (Cameroun) - Sonke, B.; Kenfack, D.; Tindo, M. (2000)
In Cameroon, parasitism by Loranthaceae is a limiting factor of the avocado tree cultivation as well as the many diseases and pests which have been better studied. Inventories were carried out in the agroecosystems of five localities around Yaounde, Cameroon. In each one of these localities, all the avocado trees likely to produce and located within a perimeter 2000 m×50 m were observed and characterized by the circumference of the trunk, the number of tufts of Loranthaceae present on the tree and of the taxon of the parasite. Avocado trees are primarily parasitized by three species of Loranthaceae. Parasitism rates (43.30-69.44%) varied significantly among the five localities of the zone studied. In addition, in each locality, this rate of parasitism varied to a significant degree according to the various classes of trunk circumference. The average number of tufts of Loranthaceae by tree was also significantly different according to locality. On a given locality scale, the variables 'average tuft number by tree' and 'trunk circumference' appeared correlated. In the absence of parasitic specificity, control has to be carried out on all the potential host species. While waiting for the avocado tree parasitism by Loranthaceae to be taken into account in the search for resistant cultivars, it is advised to control these phanerogams by carrying out a manual destruction of the tufts.